Medicaid Eligibility and Time to Re-incarceration Among Previously Incarcerated Subjects With Schizophrenia - Chris Kozma; Michael Dickson; Jacqueline Pesa; Carmela J. Benson (Journal of Health Economics and Outcomes Research)
**Background:** Many persons with severe mental illness qualify for Medicaid coverage. However, under federal law, states must either suspend or terminate eligibility once they are incarcerated. We hypothesize that prompt re-acquisition of Medicaid eligibility following release from incarceration lowers the risk of re-incarceration.